2012
DOI: 10.5194/hessd-9-13519-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supplemental irrigation potential and impact on downstream flow of Karkheh River Basin of Iran

Abstract: Supplemental irrigation of rainfed winter crops improves and stabilizes crop yield and water productivity. Although yield increases by supplemental irrigation are well established at the field level, its potential extent and impact on water resources at the basin level are less researched. This work presents a GIS-based methodology for identifying areas that are potentially suitable for supplemental irrigation and a computer routine for allocating stream flow for supplemental irrigation in different subbasins.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This approach can guide policy-makers who have to decide for EFRs values in different river basins where ecological and hydrological data are poor and it could be a starting point to implement EFRs at river basin level with "fair" ecological conditions. In future global EF assessments, it will be important to consider the inter-annual variability of flow regimes because EFRs are usually calculated on a long period average (> 20 years) and they might need to be refined for dry years (Hessari et al, 2012). Regarding the use of ecological data sets, it is worth considering the delay in ecosystem response related to flow events when calculating EFRs (Sun et al, 2008).…”
Section: Refining Global Water Assessmentsmentioning
confidence: 99%
“…This approach can guide policy-makers who have to decide for EFRs values in different river basins where ecological and hydrological data are poor and it could be a starting point to implement EFRs at river basin level with "fair" ecological conditions. In future global EF assessments, it will be important to consider the inter-annual variability of flow regimes because EFRs are usually calculated on a long period average (> 20 years) and they might need to be refined for dry years (Hessari et al, 2012). Regarding the use of ecological data sets, it is worth considering the delay in ecosystem response related to flow events when calculating EFRs (Sun et al, 2008).…”
Section: Refining Global Water Assessmentsmentioning
confidence: 99%
“…Studies on this pathway discuss as possible interventions management practices for improving the timing of water supplies using supplemental irrigation or deficit irrigation. In dry regions, moisture availability, especially during critical periods, is frequently the most significant factor limiting agricultural production (Oweis, Hachum & Kijne, 1999;Hessari, Bruggeman, Akhoond-Ali, Oweis & Abbasi, 2012). Several longer-term studies, conducted in northern Syria, found that rainfall supplemented by irrigation increases water productivity (in terms of yield per unit of water consumed) in wheat systems by alleviating moisture stress during the most sensitive stages of crop growth period (Oweis et al 1999;Zhang & Oweis, 1999;Oweis & Hachum, 2003).…”
Section: Pathways To Increase Water Productivitymentioning
confidence: 99%
“…In dry regions, moisture availability, especially during critical periods, is frequently the most significant factor limiting agricultural production. Research carried out through the SWIM, CA and subsequent programs explored the extent to which supplemental irrigation, often coupled with rainwater harvesting, can enhance yields as well as water productivity in arid and semi-arid regions (e.g., Oweis et al 1999;Wani et al 2009;Hessari et al 2012).…”
Section: Increase Yield Per Unit Of Water Consumedmentioning
confidence: 99%